2020
DOI: 10.1128/mbio.00351-20
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring a Global Iron Regulon to a Uropathogen

Abstract: Pathogenicity islands and plasmids bear genes for pathogenesis of various Escherichia coli pathotypes. Although there is a basic understanding of the contribution of these virulence factors to disease, less is known about variation in regulatory networks in determining disease phenotypes. Here, we dissected a regulatory network directed by the conserved iron homeostasis regulator, ferric uptake regulator (Fur), in uropathogenic E. coli (UPEC) strain CFT073. Comparing anaerobic genome-scale Fur DNA binding with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 86 publications
3
21
0
Order By: Relevance
“…This operon is usually found in enterobacterial plasmids, and was also identified in a pathogenicity island in uropathogenic E. coli strain CFT073 [39]. We identified no CRISPR-Cas systems among the ICEs here identified.…”
Section: Resultsmentioning
confidence: 73%
“…This operon is usually found in enterobacterial plasmids, and was also identified in a pathogenicity island in uropathogenic E. coli strain CFT073 [39]. We identified no CRISPR-Cas systems among the ICEs here identified.…”
Section: Resultsmentioning
confidence: 73%
“…Recently, a relationship between stress response, iron limitation, and amino acid uptake was demonstrated ( 25 ). Banerjee et al reported that for pathogenic E. coli , survival in the urinary tract is linked to the stress response-mediated ability to increase amino acid uptake under iron-limiting conditions ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a relationship between stress response, iron limitation, and amino acid uptake was demonstrated ( 25 ). Banerjee et al reported that for pathogenic E. coli , survival in the urinary tract is linked to the stress response-mediated ability to increase amino acid uptake under iron-limiting conditions ( 25 ). It is conceivable that similar processes occur in Salmonella exposed to glyphosate, which acts as a potent iron chelator, and these would be consistent with the increased stress response and iron metabolism observed in our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we found the siderophore aerobactin operon within an ICE in E. coli strain E302 (Table S5). This operon is usually found in enterobacterial plasmids, and was also identified in a pathogenicity island in uropathogenic E. coli strain CFT073 [44]. We identified no CRISPR-Cas systems among the ICEs here identified.…”
Section: Acquisition Of Additional Traits By Ices Include Competitivementioning
confidence: 73%